About the traces of Genoese presence along the western coast of Black Sea in 13–14 centuries. Ruins of the castle in Enisala in Dobrudja - Quirini-Popławski, Rafał (Balcanica Posnaniensia. Acta et studia, 2009)
In the second half of the 13th century, a period of intense Genoese expansion in the Black Sea basin began, resulting in the creation of an extensive network of trading posts, colonies, and fortresses. While numerous traces of this activity are well known from the Crimea and the region of Trebizond, much less is known about the Genoese presence along the western coast of the Black Sea. The aim of this study is to analyze the origins and character of the ruins of the castle in Enisala (present-day Romania, Dobruja) and to determine whether it can be associated with Genoese activities in the region. The research is based on a critical analysis of written sources (including the chronicle of Sükrüllah, travelers’ accounts, and archaeological studies by R. Ciobanu and P. Stringa) as well as comparative architectural studies of Genoese and Byzantine fortifications. The author also uses archaeological, topographical, and numismatic evidence to reconstruct the historical and functional context of the site. The study challenges the Genoese origin of the castle, suggesting instead that it was built in the second half of the 14th century on the initiative of the rulers of Dobruja — the despot Dobrotitsa or his successors. The analysis of the layout of walls, towers, and gates reveals stronger similarities to Byzantine-Balkan fortifications than to typical Genoese structures. The fortress most likely served a strategic role within the defense system of northern Dobruja rather than as a commercial or colonial establishment. These findings lead to a revision of previous views on the extent of Genoese colonization in the region, indicating that the western coast of the Black Sea was more likely under indirect political influence than a site of permanent Ligurian settlement.